Dimensions of the influence of the virtualisation of consumption on the decision-making of young Polish consumers - Zalega, Tomasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The expansion of the Internet has undoubtedly contributed to the fast development of a trend known as virtualisation of consumption. This consumer trend is primarily followed by young consumers. Their use of the Internet has led to improvements to the consumption process and facilitated their access to unlimited sources of information, consumer goods and services. Information and communication technologies make it easier and faster for young consumers to access rich sources of information about products and services offered on the web. Consequently, consumer choice increases, expanding opportunities for online shopping. In this way, consumption styles may be personalised as young consumers are more and more eager to shop online with home delivery of the goods so purchased. It should also be noted that young online shoppers have easier access to product innovations and can themselves generate such innovations by posting their opinions about specific offers. The objective of the article is to identify how virtualisation of consumption influences the decision-making of young Polish consumers. The first section explains what virtualisation of consumption essentially involves as an alternative consumer trend. In the second part, the research conceptualisation and the research sample selection and characteristics are outlined, and then the concentration is on the use of the Internet by young people and the implementation of virtualisation processes in consumer behaviours of this age group.

Rozwój Internetu niewątpliwie przyczynił się do dynamicznego rozwoju trendu zwanego wirtualizacją konsumpcji. Temu trendowi konsumenckiemu ulegają przede wszystkim młodzi konsumenci. Korzystanie przez nich z Internetu doprowadziło do usprawnienia procesu konsumpcji i ułatwiło im dostęp do nieograniczonych źródeł informacji, dóbr konsumpcyjnych i usług. Technologie informacyjno-telekomunikacyjne ułatwiają młodym konsumentom szybki dostęp do bogatych źródeł informacji o produktach i usługach oferowanych w sieci. Zwiększają się zatem możliwości wyboru konsumentów, a co zatem tym idzie, robienie zakupów online. To z kolei umożliwia zindywidualizowanie stylu konsumpcji, gdyż młodzi konsumenci coraz chętniej korzystają z zakupów robionych przez Internet z opcją dostarczenia zakupionych towarów do domu. Należy także zauważyć, że młodzi konsumenci dokonujący zakupu za pośrednictwem Internetu mają łatwiejszy dostęp do innowacji produktowych, a także sami, przez zamieszczanie opinii o określonej ofercie, mogą te innowacje generować. Celem artykułu jest uchwycenie wymiarów wpływu wirtualizacji konsumpcji na podejmowanie decyzji przez młodych polskich konsumentów. W pierwszej części opracowania skupiono się na wyjaśnieniu istoty wirtualizacji konsumpcji jako alternatywnego trendu konsumenckiego. W kolejnej drugiej, po omówieniu konceptualizacji badań i doboru próby badawczej i jej charakterystyki, skoncentrowano się na wykorzystywaniu Internetu przez osoby młode oraz na implementacji procesów wirtualizacji w zachowaniach konsumenckich tej grupy wiekowej.
Keywords: young people; virtualisation of consumption; multichannelling; showrooming; webroomiong; osoby młode; wirtualizacja konsumpcji; zakupy multikanałowe; showrooming; webroomiong